Diabetes and its prevention: pragmatic solutions for people with schizophrenia. - Gough, S; Peveler, R (2004)
BACKGROUND: Patients with schizophrenia have an increased risk of developing diabetes. However, no pragmatic pathway of care has ever been proposed in order to identify individuals at risk and manage that risk effectively. AIMS: To develop practical recommendations for the screening and management of diabetes in schizophrenia. METHOD: Staged review of evidence for the under recognition of diabetes in people with schizophrenia and of the applicability of current screening strategies to this population. Recommendations for pragmatic pathways of care were developed. RESULTS: All patients with schizophrenia should be screened and managed as a high-risk group for the development of diabetes. Psychiatrists should be responsible for screening and diabetes risk management; primary care physicians and/or diabetologists should be responsible for managing diabetes. Choice of antipsychotics should be based on achieving good control of schizophrenia, which may improve compliance with diabetes risk reduction strategies. CONCLUSIONS: Effective multidisciplinary team working should reduce the burden of diabetes in schizophrenia.